Changing Concepts of Time - Innis, Harold A. (Rowman & Littlefield Publishers, 2004)
This classic book, Harold Innis's last, returns to print with a new introduction by James Carey. An elaboration of Innis's earlier theories, Changing Concepts of Time looks at then-new technological changes in communication and considers the different ways in which space and time are perceived. Innis explores military implications of the U.S. constitution, freedom of the press, communication monopolies, culture, and press support of presidential candidates, among other interesting and diverse topics.